The redia, cercaria and early stages of Aporocotyle simplex Odhner, 1900 (Sanguinicolidae) — A digenetic trematode which has a polychaete annelid as the only intermediate host - Køie, M. (Ophelia, 1982)
An apharyngeate furcocercous cercaria which develops in the polychaete Artacama proboscidea Malmgren, 1865 (Annelida, Terebellidae), is shown experimentally to develop into Aporocotyle simplex Odhner, 1900 (Trematoda, Sanguinicolidae). A. simplex is a common blood fluke in Hippoglossoides platessoides (Fabricius), Limanda limanda (L.), and Pleuronectes platessa L. from Danish waters. About 7 % of A. proboscidea from Øresund were infested. At least two redial generations occur. More than 1000 rediae were found commonly in individual polychaetes. The rediae, which occur free in the coelomic cavity, castrate the host. The redia, cercaria and young specimens from fish are described. Both light microscopy and scanning electron microscopy were used. The cercaria has a cephalic organ with 6–9 circlets of spines. Similar spines are common on the anterior half of the body. Five pairs of penetration glands occur in the body, and one pyriform gland occurs entirely within the cephalic organ. The digestive system consists of a long oesophagus and two short caeca. The anterior part of the cercaria has a pitted tegument similar to that of schistosome cercariae. L. limanda, P. platessa and Platichthys flesus (L.) were used as experimental hosts. The cercaria penetrates the skin of the fishes, and up to six-month-old worms were found in the lymphatic system all over the fish body. Half of the 132-day-old specimens occurred in the branchial vessels. Six-month-old specimens from both the lymphatic and the blood system had uterine eggs. During the first two-three months in the fish host, long pointed spines appear on tubercles laterally, and the body shape changes from cylindrical to lanceolate. The cephalic spines remain throughout the life of the worm. The cercaria of A. simplex is compared with other marine sanguinicolid cercariae and especially with the three cercariae previously described from polychaetes. The holotype of Cercaria hartmanae Martin, 1952 was reexamined. The phylogeny of blood flukes (Sanguinicolidae, Spirorchiidae and Schistosomatidae) based on the developmental stages in the intermediate hosts is discussed.